Efectividad de la fertilización nitroazufrada sobre el rendimiento de mazorcas del maíz INIAP 543-qpm en épocas seca y lluviosa - Torres Mendoza, Alan Josué (2023)
The objective of the research was to evaluate the effectiveness of nitrosulfur fertilization on growth, yield and profitability of INIAP 543-QPM corn during the dry and rainy seasons in the Carrizal River valley. Factorial treatments of nitrogen levels (50, 100, 150 and 200 kg ha-1) and sulfur (30, 60 and 90 kg ha-1) were evaluated, plus a control treatment with omission of N and S. A design was used of complete random blocks with factorial arrangement A x B + N. The main variables recorded were yield of commercial ears, agronomic efficiency of nitrogen (EAN) and sulfur (EAS); and economic profitability. The results showed that nitrogen and sulfur fertilization significantly influenced (p<0.05) the yield of commercial ears, where the highest averages were achieved by the levels of 100 and 60 kg of nitrogen and sulfur ha-1, respectively. The EAN and EAS were inversely proportional to the levels of nitrogen and sulfur evaluated, where the levels of 50 and 30 kg of nitrogen and sulfur ha-1 achieved the highest averages of EAN and EAS, in their respective order. From an economic point of view, doses of 100 and 60 kg ha-1 of nitrogen and sulfur are more convenient for the fertilization of INIAP 543 – QPM corn. Above these doses, the economic profitability decreases.